2002
DOI: 10.1097/00004691-200210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Intraoperative Neurophysiologic Monitoring of the Spinal Cord

Abstract: Intraoperative neurophysiologic monitoring (INM) using somatosensory and motor evoked potentials (MEPs) has become popular to reduce neural risk and to improve intraoperative surgical decision making. Intraoperative neurophysiologic monitoring is affected by the choice and management of the anesthetic agents chosen. Because inhalational and intravenous anesthetic agents have effects on neural synaptic and axonal functional activities, the anesthetic effect on any given response will depend on the pathway affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
200
1
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(214 citation statements)
references
References 36 publications
1
200
1
12
Order By: Relevance
“…Heyer [2] suggested that successful monitoring has been accomplished at T1 between 5% and 50% of baseline. Usually, the variability in MEP amplitude decreases with lower NMB levels [12], and we presumed that T1/Tc 50% would allow for successful MEP monitoring and detection of any inter-group variability differences; in fact, with the NMB levels set at T1/Tc 50%, MEP monitoring was successful in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heyer [2] suggested that successful monitoring has been accomplished at T1 between 5% and 50% of baseline. Usually, the variability in MEP amplitude decreases with lower NMB levels [12], and we presumed that T1/Tc 50% would allow for successful MEP monitoring and detection of any inter-group variability differences; in fact, with the NMB levels set at T1/Tc 50%, MEP monitoring was successful in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some neuromuscular blockade (NMB) drugs significantly influence MEP monitoring during anesthesia [2,3]. However, if no NMB drug is used, higher levels of anesthetics are required to avoid the risk of spontaneous movement during surgery.…”
Section: Intraoperative Neurophysiologic Monitoring (Inm) Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…The more synapses in the neurological pathway that is being monitored, the more marked the effect on latency and amplitude of the EPs. 5 Generally, anaesthetic agents will cause an increase in latency and a decrease in the amplitude of EPs.…”
Section: The Effect Of Anaesthesia On Evoked Potentialsmentioning
confidence: 99%
“…6 SSEPs are intermediate in sensitivity and depend on the type of agents used. 5 MEPs are dependent on a functioning NMJ, and may be totally abolished during the use of NMAs. Transcranial MEPs in children can be significantly depressed, with the use of halogenated agents at lower concentrations than those in adults.…”
mentioning
confidence: 99%